Analysis of Students' Analytical Thinking Ability in Solving Number Content Numeration Problems - Holidi, Robial; Fuady, Anies (Pendidikan Matematika UNIMOR, 2025)
This study aims to describe the analytical thinking skills of class VIII A students of MTs N 1 Sarolangun in the 2024/2025 academic year in the second semester. Analytical thinking skills include identification, understanding, analysis, and problem-solving in an orderly and logical manner. The method used is descriptive qualitative. The instruments used in this study were tests and interviews. Data collection techniques in the form of analytical thinking ability tests for 27 students and interviews for six students. Data analysis was carried out through data reduction, presentation, and conclusion. The study results showed that students with analytical thinking skills were still in three categories, namely low, medium, and high analytical thinking skills. However, slightly more are in the medium category that meets the differentiating and organizing indicators. Therefore, learning improvements are needed to improve analytical thinking skills.